Harvesting well-being: an exploration of community considerations in farming decisions across diverse social-ecological contexts - Francois, Jean Ribert (My University, 2025)
The historical development of agriculture in the United States has been extensively studied and well-documented in the literature. Similarly, research has thoroughly established the impacts of the U.S. agricultural sector – home to some of the most advanced farming systems in the world – on both the environment and human well-being. For example, numerous studies have explored the connections between agriculture and community well-being over the past century, often guided by the influential Goldschmidt hypothesis, which suggests that the shift toward large-scale farming operations is associated with substantial sustainability challenges for individuals and communities. These well-established negative consequences are often the result of a complex interplay of various factors and circumstances inherent in the organization, structure, and management of modern agricultural systems. Addressing these challenges requires data-driven research to inform and support potential policies and interventions to mitigate the multiple community concerns that arise from human management practices. In three specific studies, this dissertation examines the interactions between agricultural systems, farmer decision-making, and community well-being, emphasizing the extent to which and how community concerns are considered in farming decisions across different agricultural contexts in the U.S. Study 1 investigates, through spatial analysis and descriptive statistics of county-level data from 2010 to 2019, how well-being varies across communities that differ in their levels of crop diversity and productivity, and the intensity levels of farming systems. Findings suggest that community well-being is generally high across most diversity–productivity categories. However, notable exceptions and variability within groups highlight the influence of contextual factors, such as social infrastructure and economic diversification, beyond agricultural indicators alone. Next, the second study, using both interview and survey data, explores how farmers incorporate community concerns into their decisions across diverse contexts of crop diversification. The analysis identifies key themes such as economic contributions, community health, education, and community care that farmers consider when making agricultural decisions while also noting misalignment between awareness of community impacts of farming and action to include community considerations in decision-making. Lastly, study 3 investigates the core attributes of farmers and contextual factors that shape the inclusion of community considerations in farming decisions. Through modeling techniques, the analysis emphasizes the role of awareness, community values, coordination, and structural challenges in influencing individual decision-making related to considering community well-being in farming decisions. These studies, taken together, have implications for advancing the inclusion of community considerations in farming decisions, which is important for the sustainable relationship between agricultural systems and communities.
Keywords: On-farm management decisions; Community well-being; Social-ecological systems; Sustainable agriculture; Crop diversification; Agricultural landscapes